A new approach to identify similar users based on customer reviews. Issue 1 (April 2020) - Chehal, Dimple; Gupta, Parul; Gulati, Payal
Abstract: Recommender System suggests items of interest to users based on their preferences. These preferences are gauged through various sources such as purchase history, ratings, reviews and browsing behaviour. Collaborative filtering and content based filtering are the two widely used techniques that help in generating recommendations to the target user(s) by identifying similar users to target user or similar items to items of interest. Through this paper a new method to identify similar users based on the similarity of reviews has been proposed.